A Common Operational Picture in Support of Situational Awareness for Efficient Emergency Response Operations - Sophronides, Panayiotis; Papadopoulou, Chrysaida-Aliki; Giaoutzi, Maria; Scholten, Henk J (Journal of Future Internet, 2017)
Efficient emergency response needs a multi-disciplinary approach which in turn calls for a high level of collaboration and coordination among the involved safety agencies. Furthermore, in order to cope with the complexity, uncertainty and dynamic nature of an emergency, flexible information and communication systems are required. Based on experiences from the military domain, strategic concepts which can improve information sharing and collaboration can be derived and adapted towards enhancing emergency response information systems and operational effectiveness. This study purports to review the state of the art in this field providing recommendations for emergency response policy makers, professionals and researchers.